2016
DOI: 10.1016/j.heares.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in auditory processing in the inferior colliculus of Eptesicus fuscus

Abstract: Eptesicus fuscus is typical of temperate zone bats in that both sexes undergo marked seasonal changes in behavior, endocrine status, and reproductive status. Acoustic communication plays a key role in many seasonal behaviors. For example, males emit specialized vocalizations during mating in the fall, and females use different specialized vocalizations to communicate with infants in late spring. Bats of both sexes use echolocation for foraging during times of activity, but engage in little sound-directed behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Decreased foraging in turn decreases the probability of predatory encounters and increases the likelihood of females surviving to give birth to their offspring. However, after giving birth, lactating mothers have an increased metabolic need, correlated with an increase in auditory neuron sensitivity, to promote foraging behavior and protect against predation ( Miller et al. 2016 ).…”
Section: Contextualizing Through Our Frameworkmentioning
confidence: 99%
“…Decreased foraging in turn decreases the probability of predatory encounters and increases the likelihood of females surviving to give birth to their offspring. However, after giving birth, lactating mothers have an increased metabolic need, correlated with an increase in auditory neuron sensitivity, to promote foraging behavior and protect against predation ( Miller et al. 2016 ).…”
Section: Contextualizing Through Our Frameworkmentioning
confidence: 99%
“…Brain and liver were commonly used to investigate seasonal differences in gene expression (e.g., Gillen et al, 2021 ; Johnston et al, 2016 ; Schwartz et al, 2013 ; Xiao et al, 2015 ; Zhao et al, 2016 ). In this study, we also included cochlea tissue because previous studies have indicated seasonal changes in echolocation calls and auditory processing in bats (Grilliot et al, 2014 ; Miller et al, 2016 ). Based on the similarity and difference in phenological effects between spring and autumn (see above), we further tested for the following two predictions.…”
Section: Introductionmentioning
confidence: 99%